2001
DOI: 10.3353/omp.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in the Oral Cavity

Abstract: Human papillomavirus (HPV) cannot be efficiently propagated in tissue cultures or animal models. However, molecular biological technology has made it possible to clone viral genomes, which can then be compared and also used as reagents in clinical and epidemiological studies.Today HPV infections are recognized as being responsible for inducing cancers worldwide and it is expected that HPV-based technologies will provide the tools to prevent and treat HPV-induced cancers. In this review, we focus on the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
17

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 135 publications
(232 reference statements)
0
13
0
17
Order By: Relevance
“…Among the factors that generate controversy about HPV prevalence in the normal oral mucosa seen on Table 1, we can stress the large variation in HPV detection rates, from 0% to 100% despite the use of more sensitive methods -such as PCR; another factor is the relationship between results and sample sizes, which varied in 3 samples, with 100% positiveness for HPV in the Tominaga et al 64 study from 1996, reaching up to 212 samples with 15% of HPV detection in the Kellokoski et al 65 study from 1992, thus showing a great difference between the results, which is probably due to a failure in the HPV detection methods or in harvesting the material or, even, because we do not know the exact HPV infection pathway in the normal oral mucosa 32,13,16 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Among the factors that generate controversy about HPV prevalence in the normal oral mucosa seen on Table 1, we can stress the large variation in HPV detection rates, from 0% to 100% despite the use of more sensitive methods -such as PCR; another factor is the relationship between results and sample sizes, which varied in 3 samples, with 100% positiveness for HPV in the Tominaga et al 64 study from 1996, reaching up to 212 samples with 15% of HPV detection in the Kellokoski et al 65 study from 1992, thus showing a great difference between the results, which is probably due to a failure in the HPV detection methods or in harvesting the material or, even, because we do not know the exact HPV infection pathway in the normal oral mucosa 32,13,16 .…”
Section: Discussionmentioning
confidence: 90%
“…In the normal oral mucosa we have seen a great variation in HPV rates detected, from 22% to 60% 17 ; from 0% all the way to 81.1% in studies using different methods, and with a limited number of individuals, and this seems to depend on the population studied and the choice of method 16,21 . It has been suggested that HPV prevalence in the normal mucosa includes subclinical and/or latent infections, and that the infection with a low number of virus copies is common in the oral cavity 8 .…”
Section: Human Papillomavirus Prevalence In Normal Oral Mucosamentioning
confidence: 98%
See 2 more Smart Citations
“…As oncoproteínas virais E6 e E7 são as mais importantes nesse processo, pois são capazes de ligarem-se às proteínas p53 e pRb, respectivamente, e interferirem em suas funções normais (23,26) . Além disso, a proteína E6 também apresenta importante papel na ativação da telomerase, contribuindo para o processo de imortalização dos ceratinócitos (11) .…”
Section: Introductionunclassified